DreamEden - Ty-Casper, Linda. 4 0 16; 5 (Seattle : University of Washington Press, 1996)
The conflicting lives and ambitions of various characters are thrown together by revolutionary change in the Philippines in the 1980s and 1990s.
Adult;Adult
Keywords: 2 -- 0; 6; Revolutions;Revolutions;Historical fiction.;Legal stories. -- Philippines;Philippines -- Fiction.;Fiction.; History;Politics and government;History;Politics and government -- Philippines;Philippines;Philippines;Philippines -- 1986-;1986- -- Fiction.;Fiction.;Fiction.;Fiction.; Historical fiction.;Legal stories